An evaluation of trial‐based functional analyses of inappropriate mealtime behavior. Issue 1 (18th November 2021) - Andersen, Ashley S.; Hansen, Bethany A.; Peterson, Kathryn M.
Abstract : Functional analyses allow clinicians to develop treatment targeting the variables maintaining a child's inappropriate mealtime behavior (Bachmeyer et al., 2019). Extended functional analyses can be inefficient, potentially delaying the onset of treatment. Researchers have suggested a trial‐based functional analysis can increase assessment efficiency (Saini, Fisher, et al., 2019). This study compared trial‐based functional analyses to extended functional analyses to determine the variables maintaining inappropriate mealtime behavior. We compared the efficiency and acceptability and evaluated treatments informed by the analyses. Exact correspondence between analyses was low (29%); however, most treatments indicated by the trial‐based functional analyses (80%) resulted in improvements in the child's target behavior. The trial‐based functional analysis required 71% less time than the extended functional analysis, and caregivers found analyses equally acceptable. Future researchers should continue refining trial‐based functional analysis procedures to provide an efficient assessment that leads to efficacious treatment.